Improving Science And Sosiality Learning Outcomes Through The Project Based Learning Model - Sri Mulyani (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The purpose of this study was to improve the learning outcomes of students in the Science and Technology section in grade IV elementary schools using the Project Based Learning (PjBL) learning model. This research is a class action research (CAR) for two cycles. Data collection techniques are observation, interviews, documentation, and tests. At the time of pre-action the average value of 58 in cycle 1 increased to 69 and in cycle II increased to 80. The percentage of completeness of students before the action (pre-cycle) students scored above the minimum completeness criteria (KKM), namely 70 only 6 students (30%) in cycle I as many as 10 students (50%) scored above KKM, in cycle II as many as 17 students (85%) obtained above KKM. This shows that the use of Project Based Learning (PjBL) learning model can improve student learning outcomes in class IV Science Science subjects at SDN 1 Keposong.